High ductile behavior of a polyethylene fiber-reinforced one-part geopolymer composite: A micromechanics-based investigation - Nematollahi, Behzad (2017)
This study investigates the tensile performance a one-part strain hardening geopolymer composite (SHGC) reinforced by ultra-high-molecular-weight polyethylene (PE) fibers. The developed composite as a “dry mix” uses a small amount of solid activator rather than large quantities of commonly used alkaline solutions and eliminates the necessity for heat curing. The quantitative influences of curing condition (heat and ambient temperature curing) and type of fiber (poly vinyl alcohol (PVA) and PE fibers) on the macroscale properties of the matrix and composite including workability, density, compressive strength, and uniaxial tensile performance were evaluated. A micromechanics-based investigation was performed to explain the experimentally observed macroscopic high tensile ductility of the developed one-part PE-SHGCs. The investigation involved determination of the matrix fracture properties and the fiber–matrix interface properties using fracture toughness tests and single-fiber pullout tests, respectively. The fiber-bridging constitutive law of the composites was computed via a micromechanics-based model to link the material microstructures to macroscopic composite tensile performance. The results indicated that the ambient temperature curing increased the compressive and tensile strengths, but reduced the tensile ductility of the one-part PE-SHGCs. The one-part PE-SHGCs exhibited lower compressive and tensile strengths, but higher tensile ductility compared to the one-part PVA-SHGC.